2014
DOI: 10.1111/caim.12083
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Network Capability and Their Effects on Innovation Performance: An Empirical Test of Hi‐tech Firms in China

Abstract: A firm's competitive advantage can come not only from internal resources but also from inter‐firm innovation networks. This paper shows that network capabilities (i.e., network visioning capability, network constructing capability, network operating capability and network centring capability) are special skills that enable values residing in network resources. Based on a sample of 211 Chinese hi‐tech firms and by applying structural equation modelling, network capabilities are found to have a positive relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 86 publications
(176 reference statements)
0
29
0
Order By: Relevance
“…The first step in SEM is to assess the overall model fit with some fit indices (Fang et al 2014). The overall goodness of fit indices indicates that the hypothesized models are good representations of the structures underlying the data (Baumgartner and Homburg 1996).…”
Section: Resultsmentioning
confidence: 99%
“…The first step in SEM is to assess the overall model fit with some fit indices (Fang et al 2014). The overall goodness of fit indices indicates that the hypothesized models are good representations of the structures underlying the data (Baumgartner and Homburg 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Based on a literature review, Niesten and Jolink (2015) [47] unveiled a same explanatory mechanism for the impact of network management capabilities on performance. In addition, the results of a relevant study, which identified some antecedents of network capabilities [74], would also alleviate the possibility of presence of reverse causality.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a literature review, Niesten and Jolink (2015) [47] unveiled a same explanatory mechanism for the impact of network management capabilities on performance. In addition, the results of a relevant study, which identified some antecedents of network capabilities [74], would also alleviate the possibility of presence of reverse causality.…”
Section: Discussionmentioning
confidence: 99%